Motivation as a Determinant of Employee Performance - Dio Alif Ramadhan; Faizal Mulia Z; Nor Norisanti (Almana : Jurnal Manajemen dan Bisnis, 2021)
In the background here, the problem is that the dependent variable is employee performance and the independent variable is motivation. The purpose of this study was to determine the effect of motivation on the employee performance of PT. Arta Boga Cemerlang Depo Sukabumi. This research uses quantitative methods. The population in this study was PT. Arta Boga Cemerlang Depo Sukabumi Employee and the sample used was 86 respondents. The data analysis technique used is simple linear regression analysis and the sampling technique used is the random sampling method. The results of this study indicate that motivation has a significant and positive influence on employee performance. The results of the T-test, namely the value of Tcount 3.276> 1.989 indicate that Tcount is greater than T-table and the results of the correlation in this study have a medium value of 0,692, so it can be concluded that the variable motivation influences employee performance.